Rule-based exposure assessment versus case-by-case expert assessment using the same information in a community-based study. Issue 3 (12th November 2013) - Peters, Susan; Glass, Deborah C; Milne, Elizabeth; Fritschi, Lin; ,
Abstract : Background: Retrospective exposure assessment in community-based studies is largely reliant on questionnaire information. Expert assessment is often used to assess lifetime occupational exposures, but these assessments generally lack transparency and are very time-consuming. We explored the agreement between a rule-based assessment approach and case-by-case expert assessment of occupational exposures in a community-based study. Methods: We used data from a case–control study of childhood acute lymphoblastic leukaemia in which parental occupational exposures were originally assigned by expert assessment. Key questions were identified from the completed parent questionnaires and, on the basis of these, rules were written to assign exposure levels to diesel exhaust, pesticides and solvents. We estimated exposure prevalence separately for fathers and mothers, and used κ statistics to assess the agreement between the two exposure assessment methods. Results: Exposures were assigned to 5829 jobs among 1079 men and 6189 jobs among 1234 women. For both sexes, agreement was good for the two assessment methods of exposure to diesel exhaust at a job level (κ=0.70 for men and κ=0.71 for women) and at a person level (κ=0.74 and κ=0.75). The agreement was good to excellent for pesticide exposure among men (κ=0.74 for jobs and κ=0.84 at a person level) and women (κ=0.68 and κ=0.71 at a job and person level, respectively). Moderate to good agreement was observed for assessment of solvent exposure, which was better for women than men. Conclusions: The rule-based assessment approach appeared to be an efficient alternative for assigning occupational exposures in a community-based study for a selection of occupational exposures.